Synthesis of a new series of dithiocarbamates with effective human carbonic anhydrase inhibitory activity and antiglaucoma action. Issue 10 (15th May 2015) - Bozdag, Murat; Carta, Fabrizio; Vullo, Daniela; Akdemir, Atilla; Isik, Semra; Lanzi, Cecilia; Scozzafava, Andrea; Masini, Emanuela; Supuran, Claudiu T.
Graphical abstract: Abstract: A new series of dithiocarbamates (DTCs) was prepared from primary/secondary amines incorporating amino/hydroxyl-alkyl, mono- and bicyclic aliphatic ring systems based on the quinuclidine, piperidine, hydroxy-/carboxy-/amino-substituted piperidine, morpholine and piperazine scaffolds, and carbon disulfide. The compounds were investigated for the inhibition of four mammalian α-carbonic anhydrases (CAs, EC 4.2.1.1) of pharmacologic relevance, that is, the human (h) hCA I, II, IX and XII, drug targets for antiglaucoma (hCA II and XII) or antitumor (hCA IX/XII) agents. The compounds were moderate or inefficient hCA I inhibitors (off-target isoform for both applications), efficiently inhibited hCA II, whereas some of them were low nanomolar/subnanomolar hCA IX/XII inhibitors. One DTC showed excellent intraocular pressure (IOP) lowering properties in an animal model of glaucoma, with a two times better efficiency compared to the clinically used sulfonamide dorzolamide.